Safety and effectiveness of ferric carboxymaltose intravenous therapy in pediatric patients with chronic kidney disease - Garcia-Ortega, Patricia; Jimenez-Lozano, Ines; Cruz, Álejandro; Polo, Aurora Fernandez; Lopez, Mercedes; Ariceta, Gema (Frontiers in Pediatrics, 2022)
Iron-deficiency anemia is the most common reason for worsening of the anemia characteristically seen in chronic kidney disease (CKD). Ferric carboxymaltose (FCM) is a macromolecular hydroxide ferric carbohydrate complex that allows high-dose iron to be administered parenterally for gradual, controlled release. The aim of this study was to retrospectively evaluate the safety and effectiveness of FCM treatment in pediatric patients with CKD nondependent of hemodialysis, seen at a tertiary hospital. Data were collected on demographics, dosage, infusion time, laboratory results, and tolerability of the medicinal product. A total of 79 patients (40.5% girls) were included; the median age (25th percentile [P25] to 75th percentile [P75]) was 9 years (5-13). Laboratory results at 15-45 days post-infusion revealed a median increase of 1.4 g/dL (0.9-1.9) in hemoglobin, 224 µg/L (136-378.5) in ferritin, 37 µg/dL (17.5-71) in serum iron, and 18% (9.3-27.8) in transferrin saturation. All patients tolerated FCM infusions well, and no serious hypersensitivity reactions or anaphylactic reactions were observed. Only one adverse event was identified: drug extravasation at the end of the infusion in a 16-year-old patient. These data provide further evidence for the use of FCM as a safe and effective therapeutic option in pediatric patients with CKD, based on the low incidence of adverse effects, minor intervention required, and anemia improvement based on laboratory results.